2009
DOI: 10.1158/1078-0432.ccr-09-1452
|View full text |Cite
|
Sign up to set email alerts
|

Serum Molecular Signatures of Weight Change during Early Breast Cancer Chemotherapy

Abstract: Purpose: Weight gain in women receiving chemotherapy for breast cancer is associated with a higher risk of recurrence but its mechanisms are poorly understood. Experimental Design: To investigate this, we assessed the metabolic, cytokine, and appetite-related peptide alterations during adjuvant chemotherapy for early breast cancer in postmenopausal women, and correlated these with body mass measurements. Specifically, we performed global metabolic profiling using 1 H-nuclear magnetic resonance spectroscopy of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…Adam et al showed that the power of a single variable in discriminating prostate cancer from normal patients could be determined by AUC, which ranges from 0.5 (no discriminating power) to 1.0 (complete separation) (34). Another study demonstrated that metabolite significance in differentiating weight gain group during early breast cancer chemotherapy could also be revealed by AUC (35).…”
Section: Fig 2 Pca Score Plots Based On the Data From (A) Rp Separamentioning
confidence: 99%
“…Adam et al showed that the power of a single variable in discriminating prostate cancer from normal patients could be determined by AUC, which ranges from 0.5 (no discriminating power) to 1.0 (complete separation) (34). Another study demonstrated that metabolite significance in differentiating weight gain group during early breast cancer chemotherapy could also be revealed by AUC (35).…”
Section: Fig 2 Pca Score Plots Based On the Data From (A) Rp Separamentioning
confidence: 99%
“…In the first validated study with human patients, as opposed to volunteers, Keun et al [79] used 600 MHz 1 H NMR to show that pre-treatment serum levels of alanine and lactate together with % body fat were predictive of weight gain in women undergoing chemotherapy treatment for breast cancer. This is important as weight gain is associated with a risk of cancer recurrence.…”
Section: Prediction Of Drug Safety Studiesmentioning
confidence: 99%
“…Keun and coworkers demonstrated in 2009 that serum biomarkers could be used to predict weight gain in women undergoing chemotherapy for breast cancer. 69 This represents the first validated pharmacometabonomic study with patients as opposed to volunteers. PLS-DA analysis of 600 MHz 1 H NMR spectra of serum established that pretreatment concentrations of lactate, alanine and percentage of body fat were significantly predictive of weight gain in individuals.…”
Section: Progress In Clinical Pharmacometabonomicsmentioning
confidence: 99%